Analisis Sikap Konsumen (Mahasiswa) dalam Pembelian Produk Fashion melalui Belanja Online - Mun’im, Mun’im; Kulsum, Ummi (Journal of Industrial and Syariah Economics, 2024)
This research is concerned with consumer attitudes towards online shopping and factors that influence consumers to shop online. The aim of this research is to identify and analyze the factors that influence consumers to shop online. The research method used uses a qualitative approach with a single case type case study method. The population was students from Al-Hikmah Singgahan University - Tuban, while the sample size was 20 people taken using a convenience sampling technique. From the research results, it is known that website design factors are the factors that most influence consumers' attitudes towards online shopping, followed by convenience which is the second factor that most influences online shopping attitudes, then energy saving factors and security factors.